Comparison of methods generating antibody-epitope conjugates for targeting cancer with virus-specific T cells - van der Wulp, Willemijn; Gram, Anna M.; Bleijlevens, Boris; Hagedoorn, Renate S.; Araman, Can; Kim, Robbert Q.; Drijfhout, Jan Wouter; Parren, Paul W. H. I.; Hibbert, Richard G.; Hoeben, Rob C.; van Kasteren, Sander I.; Schuurman, Janine; et al. (Frontiers in Immunology, 2023)
Therapeutic antibody-epitope conjugates (AECs) are promising new modalities to deliver immunogenic epitopes and redirect virus-specific T-cell activity to cancer cells. Nevertheless, many aspects of these antibody conjugates require optimization to increase their efficacy. Here we evaluated different strategies to conjugate an EBV epitope (YVL/A2) preceded by a protease cleavage site to the antibodies cetuximab and trastuzumab. Three approaches were taken: chemical conjugation (i.e. a thiol-maleimide reaction) to reduced cysteine side chains, heavy chain C-terminal enzymatic conjugation using sortase A, and genetic fusions, to the heavy chain (HC) C-terminus. All three conjugates were capable of T-cell activation and target-cell killing via proteolytic release of the EBV epitope and expression of the antibody target was a requirement for T-cell activation. Moreover, AECs generated with a second immunogenic epitope derived from CMV (NLV/A2) were able to deliver and redirect CMV specific T-cells, in which the amino sequence of the attached peptide appeared to influence the efficiency of epitope delivery. Therefore, screening of multiple protease cleavage sites and epitopes attached to the antibody is necessary. Taken together, our data demonstrated that multiple AECs could sensitize cancer cells to virus-specific T cells.